2015
DOI: 10.1515/cmble-2015-0008
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of PACAP for neurodegenerative diseases

Abstract: Pituitary adenylate cyclase activating polypeptide (PACAP) is widely expressed in the central and peripheral nervous system. PACAP can initiate multiple signaling pathways through binding with three class B G-protein coupled receptors, PAC1, VPAC1 and VPAC2. Previous studies have revealed numerous biological activities of PACAP in the nervous system. PACAP acts as a neurotransmitter, neuromodulator and neurotrophic factor. Recently, its neuroprotective potential has been demonstrated in numerous in vitro and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…The protective effects of PACAP in models of neurodegenerative diseases have been widely documented and its effects in models of Parkinson's, Huntington's, and Alzheimer's diseases are known (Cabezas-Llobet et al 2018;Reglodi et al 2011Reglodi et al , 2017Yang et al 2015). However, in spite of these diseases characteristically appearing in older ages, most studies have been performed in young animals, which can yield misleading extrapolations to older age groups (Tamas et al 2005(Tamas et al , 2006.…”
Section: Reversal Of Age-related Pathophysiological Changes By Pacapmentioning
confidence: 99%
“…The protective effects of PACAP in models of neurodegenerative diseases have been widely documented and its effects in models of Parkinson's, Huntington's, and Alzheimer's diseases are known (Cabezas-Llobet et al 2018;Reglodi et al 2011Reglodi et al , 2017Yang et al 2015). However, in spite of these diseases characteristically appearing in older ages, most studies have been performed in young animals, which can yield misleading extrapolations to older age groups (Tamas et al 2005(Tamas et al , 2006.…”
Section: Reversal Of Age-related Pathophysiological Changes By Pacapmentioning
confidence: 99%
“…PACAP is a member of the vasoactive intestinal peptide/secretin/growth hormone-releasing hormone/glucagon superfamily 43,44 . PACAP showed neuroprotective effects in neurodegeneration models of cerebral ischemia and brain injuries 41,4449 and in other neurological diseases such as Parkinson’s disease 5054 and Alzheimer’s disease 46,50,5459 . Nevertheless, use of PACAP in clinical practice presents some limitations because of its low stability in human plasma 60 , rapid degradation 61 and peripheral actions 6264 .…”
Section: Introductionmentioning
confidence: 99%
“…PACAP is a pleiotropic molecule, involved in a wide range of physiological processes, including cell survival during neurodegenerative conditions, stress response and cell division (Canonico et al, ; Castorina et al, ; Castorina, Giunta, Mazzone, Cardile, & D'Agata, ; Castorina, Scuderi, D'Amico, Drago, & D'Agata, ; Cavallaro et al, , ; D'Agata & Cavallaro, ; D'Agata, Cavallaro, Stivala, Travali, & Canonico, ; D'Amico et al, , ; Giunta et al, ; Maino et al, ; Maugeri, D'Amico, & Gagliano, ; Maugeri, D'Amico, & Saccone, ; Scuderi et al, ). Moreover, it is known to act as a neurotransmitter and/or a neuromodulator in the peripheral and central nervous system (Jóźwiak‐Bębenista, Kowalczyk, & Nowak, ; Shioda et al, , ; Yang et al, ). Despite recent findings have revealed that PACAP is able to rescue rat motor neurons against glutamate‐induced excitotoxicity in vitro (Tomimatsu & Arakawa, ), and confers neuroprotection to central visceromotor neurons via autocrine pathways in SOD1(G93A) mice model (Ringer et al, ), the effect of PACAP in ALS still remains unknown.…”
Section: Introductionmentioning
confidence: 99%